2013 12th International Conference on Document Analysis and Recognition 2013
DOI: 10.1109/icdar.2013.263
|View full text |Cite
|
Sign up to set email alerts
|

On Evaluation of Segmentation-Free Word Spotting Approaches without Hard Decisions

Abstract: Word spotting systems are intended to retrieve occurrences of a given keyword in document images without actually recognizing the full document content. As there is a trend towards segmentation-free word spotting methods, we propose a methodology to evaluate these methods by employing measures that take the quality of the retrieved word locations into account without making hard decisions. We derive a desired evaluation behavior with the help of synthetic examples and show discrepancies of existing evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The original methods work by locating the zones of interest through gradients, while the proposed method employs curvature according to a threshold instead. The resulting mAP based on the precision measures p IR and γ LA , presented in [115], showed that the proposed system outperformed the already existing application on the HADARA80P and the George Washington datasets.…”
Section: Hadara80pmentioning
confidence: 91%
“…The original methods work by locating the zones of interest through gradients, while the proposed method employs curvature according to a threshold instead. The resulting mAP based on the precision measures p IR and γ LA , presented in [115], showed that the proposed system outperformed the already existing application on the HADARA80P and the George Washington datasets.…”
Section: Hadara80pmentioning
confidence: 91%
“…Patnke et al [9] gave a detailed description of the HADARA dataset, including the structure, line and word segmentation, ground truth creation, and transcription of the pages, and integrated different template-based word spotting methods in their proposed method. A detailed evaluation procedure on segmentation-free word spotting methods on the HADARA dataset has been provided with equations and explanations [10].…”
Section: Training-free Methodsmentioning
confidence: 99%